Chemoenzymatic Production and Engineering of Chitooligosaccharides and N-acetyl Glucosamine for Refining Biological Activities - Kumar, Manish; Rajput, Meenakshi; Soni, Twinkle; Vivekanand, Vivekanand; Pareek, Nidhi (Frontiers in Chemistry, 2020)
In the current scenario, Chitooligosaccharides (COS) and N-acetyl glucosamine (GlcNAc) is of enormous relevance to pharmaceuticals, nutraceuticals, cosmetics, food and agriculture industries due to their wide range of biological activities viz. antimicrobial, antitumor, antioxidant, anticoagulant, wound healing, immunoregulatory and hypocholesterolemic. A range of methods have been developed for the synthesis of COS with a specific degree of polymerization along with high production titres. In this respect, chemical, enzymatic as well as microbial means along with the modern genetic manipulation techniques have been extensively explored; however none of the method has appeared competent to produce defined COS and GlcNAc in mono-system approach. Henceforth, the chitin research has turned towards increased exploration of chemoenzymatic processes for COS and GlcNAc generation. Recent developments in the area of green chemicals, mainly ionic liquids proved vital for the specified COS and GlcNAc synthesis with better yield and purity. Moreover, engineering of COS and GlcNAc to generate novel derivatives viz. carboxylated, sulfated, phenolic acid conjugated, amino derived COS, etc. further improved their biological activities. Consequently, chemoenzymatic synthesis and engineering of COS and GlcNAc emerged as a proficient approach to lead the biologically active compound based biomedical research to an advanced prospect in the forthcoming era.